Improved Fully Differential Low Power Active Filter - Imane Halkhams; Mahmoud Mehdi; Said Mazer; Moulhime El Bekkali; Wafae El Hamdani (Institute of Advanced Engineering and Science, 2017)
This paper relates the new topology and simulations of a fully differential CMOS active filter for mm wave band applications. The advantages of the differential topology over the single ended one are discussed and the quality factor is tuned to insure application requirements, including narrow bandwidth and high selectivity due to a differential negative resistance that reuses the filter’s current. Using this topology enables independent tuning of the quality factor and low power consumption while compensating the resistive loss of the filter. Very high filter performance was obtained with the simulated active inductor based active filter that was designed using CMOS 0.35 µm technology from AMS foundry and that resonates at 30 GHz with a high quality factor of Q > 500.